Conceptual model and numerical analysis of the Desert Peak EGS project: Reservoir response to the shallow medium flow-rate hydraulic stimulation phase. (September 2016) - Benato, Stefano; Hickman, Stephen; Davatzes, Nicholas C.; Taron, Joshua; Spielman, Paul; Elsworth, Derek; Majer, Ernest L.; Boyle, Katie
Highlights: A relationship between hydraulic stimulations and microseismicity is observed. Conceptual and numerical analyses are developed to explain such a connection. Results point out a key stimulation target defined as Shearing Target Fault (STF). Abstract: A series of stimulation treatments were performed as part of the Engineered Geothermal System (EGS) experiment in the shallow open-hole section of Desert Peak well 27-15 (September 2010–November 2012). These injections at variable wellhead pressures, both below and above the magnitude of the least horizontal principal stress ( S hmin ), produced injectivity gains consistent with hydraulically induced mechanical shear and tensile failure in the surrounding rock. A conceptual framework for the overall Desert Peak EGS experiment is developed and tested based on a synthesis of available structural and geological data. These data include down-hole fracture attributes, in situ stress conditions, pressure interference tests, geochemical tracer studies, and observed induced seismicity. Induced seismicity plays a key role in identifying the geometry of large-scale geological structures that could potentially serve as preferential flow paths during some of the stimulation phases. The numerical code FLAC3D is implemented to simulate the reservoir response to hydraulic stimulation and to investigate in situ conditions conducive to both tensile and shear failure. Results from the numerical analysis show that conditions for shear failure could have occurred along fractures associated with a large northeast-trending normal fault structure located ∼400 m below the injection interval which coincides with the locations of most of the observed micro-seismicity. This structure may also provide a hydrologic connection between EGS well 27-15 and injection/production wells further to the south–southwest.